Sosialisasi tentang Pentingnya Menggosok Gigi Sejak Dini di TK Yarsi Mataram - Inayati, Rizqa; Darma Isasih, Widani; Fitriana, Istin (Insan Kreasi Media, 2023)
The high incidence of cavities in children is caused by the habit of children who like sweet foods without being followed by the habit of brushing their teeth. Good and correct tooth brushing behavior is one part of efforts to maintain oral hygiene. The habit of maintaining dental and oral hygiene really needs to be instilled early on, one of the efforts that can be done is to provide knowledge about dental and oral health and how to brush your teeth properly and correctly. The purpose of this activity is to increase the knowledge and awareness of students at Kindergarten Yarsi Mataram about the importance of brushing their teeth properly and correctly, and the importance of building the habit of brushing their teeth from an early age. The methods used in this activity are playing and singing together, hands-on practice, quizzes, and giving prizes. This activity was realized through the collaboration of the service team consisting of lecturers and students. The result of this activity was an increase in awareness about the importance of brushing their teeth properly and correctly in Yarsi Mataram Kindergarten students, as well as the importance of building the habit of brushing their teeth from an early age.